Learning with self-generated drawings and the impact of learners’ emotional states - Navratil, Sabrina D.; Kühl, Tim (Frontiers in Psychology, 2023)
The present study examined the influence of emotional states when learning with self-generated drawings. It was assumed that learners in a positive emotional state would profit from learning with self-generated drawings, while learners in a negative emotional state would not profit from this strategy to the same extent but would rather benefit through reading. University students (N = 123) were randomly assigned to one of four conditions resulting from a 2 x 2 design with self-generated drawings (yes vs. no) and emotional state (positive vs. negative) as independent variables. Results showed that learning with self-generated drawings was more beneficial for a following transfer test than learning without drawings -irrespective of a learner's emotional state. The quality of selfgenerated drawings predicted the learning outcomes of the retention and pictorial test, but not for transfer. Missing effects of emotional states and the missing interaction with self-generated drawings will be discussed.